Functions of the metaphor in the innovation process at the lexical and the semantic levels of the Russian language - Vanya Ivanova (Проглас, 2021)
The article examines the nominative and the characterizing functions of metaphors in the innovation process at the lexical and the semantic levels of the Russian language at the beginning of the 21st century. It also discusses the manifestation of the metaphorical function in the emergence of semantic innovations on the basis of metaphorization, as well as in the integration of foreign language semantic elements with metaphorical grounds. The simultaneous manifestation of these two functions in the nomination and characterization of the newly-emerged realia at the beginning of the 21st century is traced as well. The function of metaphorical nomination is also considered in connection with the spheres of dissemination of semantic innovations.